Social Integration in Higher Education and Development of Intrinsic Motivation: A Latent Transition Analysis - Reindl, Marion; Auer, Tanja; Gniewosz, Burkhard (Frontiers in Psychology, 2022)
The present study, based on self-determination theory, investigates the link between university students’ social peer and teacher integration and intrinsic motivation development. Both integration contexts are expected to contribute to the student’s development, either additive or compensatory. The analyses rely on a nationally representative sample of 7619 German university students (NEPS data set) and cover the time span between the 3rd and 5th semester in a longitudinal design. Person-centered analytical tools were applied to tap interindividual differences in the motivational trajectories as well as in integration profiles. Latent transition analyses revealed distinct links between the motivational trajectories (Increase [n = 532], Moderate Decrease [n = 2580], Decrease [n = 4507]) and the integration profiles (Highly Integrated [n = 2492], Moderately Integrated [n = 3832], Isolated [n = 1144], Peer Deprivated [n = 151]), pointing to additive effects of teacher and peer integration. Positive trajectories were more likely in the Highly than in Moderately Integrated profiles. The two profiles pointing to below average integration levels (Isolated and Peer Deprivated) showed the same probabilities for rather negative trajectories. The results are discussed against the backdrop of self-determination theory and additive vs. compensatory effects of teacher and peer integration, proposing a threshold model.